Pakistan's Nuclear Program: The Context. (1st January 2016) - ,
Abstract : The main driver of Pakistan's nuclear weapon program is existing military threat emanating from India's conventional and nuclear military capabilities. Though India often cites Chinese nuclear weapons program as the main driver for its nuclear weapons' pursuits, India's Program was on sound footings well before China's nuclear test in 1964. New Delhi's decision to go nuclear had provided Islamabad a God-sent opportunity to pullout its nuclear Program from the shadow of ambiguity and lay claims over comparable capability and capacity. For Pakistan, there was just one reason for wanting "The Bomb" that Indian Nuclear had to be countered by Pakistani nuclear, for nuclear could only be countered by nuclear. India's nuclear Program is status driven, something it thinks would place it into a permanent seat at the United Nations Security Council (UNSC). Ironically Pakistan's necessity driven nuclear Program continues to draw ire. While at the same time, India's luxury driven nuclear Program is being afforded further enablers. Pakistan has expressed willingness to join the Comprehensive Test Ban Treaty (CTBT) simultaneously with India. Furthermore, India's dangerous doctrinal orientations and US 120 billion modernization and up-gradation Programs have upped the asymmetry in conventional domain vis-a-vis Pakistan. Therefore, Pakistan views deterrence through a comprehensive lens comprising conventional and nuclear capabilities. The international community needs to view Pakistan's nuclear weapon program in the context of the threat it faces. The civilian component of nuclear program is aimed at enabling Pakistan to overcome its energy shortage through nuclear fuel.